2004
DOI: 10.1029/2004jd004547
|View full text |Cite
|
Sign up to set email alerts
|

First comparison between ground‐based and satellite‐borne measurements of tropospheric nitrogen dioxide in the Po basin

Abstract: [1] In this paper we present in situ and tropospheric column measurements of NO 2 in the Po river basin (northern Italy). The aim of the work is to provide a quantitative comparison between ground-based and satellite measurements in order to assess the validity of spaceborne measurements for estimating NO 2 emissions and evaluate possible climatic effects. The study is carried out using in situ chemiluminescent instrumentation installed in the Po valley, a UV/Vis spectrometer installed at Mount Cimone (44.2°N,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
65
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(74 citation statements)
references
References 36 publications
8
65
0
1
Order By: Relevance
“…The normalised seasonal variation of the ground-based data agrees reasonably well with the variation observed by GOME, in particular regarding the large differences between summer and winter. Similarly pronounced seasonal variations of space-borne NO 2 VTCs over industrialised regions have also been reported by Petritoli et al (2004), Richter et al (2005), van der A et al (2006) and Uno et al (2006). The seasonal amplitude in the SCIAMACHY data, however, is lower than in both GOME and ground-based observations: For the median values the amplitude is reduced by more than a factor of two.…”
Section: Comparison Of Gome and Sciamachy No 2 Vtcssupporting
confidence: 76%
“…The normalised seasonal variation of the ground-based data agrees reasonably well with the variation observed by GOME, in particular regarding the large differences between summer and winter. Similarly pronounced seasonal variations of space-borne NO 2 VTCs over industrialised regions have also been reported by Petritoli et al (2004), Richter et al (2005), van der A et al (2006) and Uno et al (2006). The seasonal amplitude in the SCIAMACHY data, however, is lower than in both GOME and ground-based observations: For the median values the amplitude is reduced by more than a factor of two.…”
Section: Comparison Of Gome and Sciamachy No 2 Vtcssupporting
confidence: 76%
“…Observations of a weekly pattern in GOME tropospheric NO 2 columns with significant reductions on weekends [Beirle et al, 2003], diurnal variation in NO 2 columns driven by emissions and photochemistry [Boersma et al, 2008a], and a large increase in tropospheric NO 2 columns over eastern China inferred from GOME and SCIAMACHY [Richter et al, 2005;van der A et al, 2006] demonstrate the capability of observing air pollution from space. Petritoli et al [2004] and Ordóñez et al [2006] found a significant correlation between in situ NO 2 measurements and GOME tropospheric NO 2 columns. Airborne measurements in the southeastern United States reveal that NO 2 in the boundary layer can make a dominant contribution to the NO 2 tropospheric column over polluted regions [Martin et al, 2004a;Bucsela et al, 2008].…”
Section: Introductionmentioning
confidence: 91%
“…But validation efforts for various retrievals show acceptable accuracy (Heland et al, 2002;Petritoli et al, 2004;Martin et al, 2004Martin et al, , 2006Petritoli et al, 2005;Cede et al, 2006;Ordóñez et al, 2006;Schaub et al, 2006) for GOME and SCIAMACHY NO 2 .…”
Section: Introductionmentioning
confidence: 99%